Translation of Postpartum Bonding Questionnaire (PBQ) In Urdu Language - Israr, Raazia (Journal of Peace, Development and Communication, 2021)
Postpartum Bonding Questionnaire (PBQ) was widely used to measure the emotional thoughts of mothers towards the infant. Postpartum Bonding Questionnaire is helpful for the assessment of mother-infant bonding problems in mothers with postpartum depression. Therefore it is necessary to translated PBQ into Urdu language to make it understandable for Pakistani mothers. In the present study, Postpartum Bonding Questionnaire (PBQ) developed by Brockington et al. (2001) and revised by Brockington, Fraser and Wilson (2006) was translated for the assessment of mother-infant bonding problems in a sample of Pakistani postpartum mothers with postpartum depression. Four hundred postpartum mothers were screened on Edinburgh Postnatal Depression Scale (EPDS) and 150 depressed mothers of age range 18 to 45 years were selected to participate in the study through purposive sampling technique. PBQ was translated into Urdu using Back-translation method of Brislin (1976). The alpha reliability coefficients for the subscales of Postpartum Bonding Questionnaire Urdu –version were ranged from .33 to .93. Findings also showed that PBQ has satisfactory internal validity. The PBQ Urdu-version would be very useful for identifying problems of the mother-infant bonding in mothers with postpartum depression. In the future researches PBQ Urdu-version would also be useful for the researchers working in the same area. Keywords: Postpartum Bonding Questionnaire, Edinburgh Postnatal Depression Scale, purposive sampling technique, alpha reliability coefficients, internal validity